The designation of an area to be protected according to the landscape's water component: THE DESIGNATION OF AN AREA TO BE PROTECTED ACCORDING TO THE LANDSCAPE'S WATER COMPONENT - Follmann, Fernanda Maria (2021)
In shaping landscapes, abiotic, biotic, and anthropic components must be interconnected, interacting with one another and providing environmental services that are widely used by populations. As a result of the intense degradation of environmental systems caused by humans, there is a need to identify areas for environmental protection, based on the choice of landscape components and an appropriate theoretical and methodological framework in accordance with the analyzed area. This paper aims to discuss the identification of an area - part of Annex 12 of the Santa Maria Land Use and Occupation Act, Rio Grande do Sul, Brazil - to be protected in a territorial zone, considering its water component. This component is of fundamental importance for providing environmental services to the population. The research was developed using the multicriteria analysis methodological strategy and established the following criteria for mapping: areas with relevance in water supply, and distance from water resources. The results showed areas of significant impact in the region presented in Annex 12, which should be considered in determining the management strategies involving land use or restrictions. Thus the conceptual basis, the methodological technique, and the results obtained will contribute to designating a local area to be protected in the region.